2022
DOI: 10.1111/wvn.12582
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of patient education for pressure injury: Evidence to guide practice

Abstract: Background: Pressure injuries (PIs) are generally regarded as predictable and preventable. Therefore, providing appropriate care for PI prevention and its management is vital. Patient education is a significant component of the PI international guideline-recommended strategy in preventing PIs. Despite the availability of evidence supporting patient education, consensus regarding the effect of patient education on knowledge, patient participation, wound healing progress, and quality of life is still lacking. Ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…These associations suggest that the measure of success in patient education is in improving patient and carer knowledge and skills in managing PI, as well as patient behavioural change associated with prevention, improvements in quality of life and evidence that the education programme has reduced or prevented the incidences of PI. 12 The objective is also to focus on providing information that encourages active engagement in patients' selfcare and decision-making. 13 Despite these recommendations, a study by Team et al 14 identified deficits in the uniformity and quality of patient education in the prevention of PIs.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…These associations suggest that the measure of success in patient education is in improving patient and carer knowledge and skills in managing PI, as well as patient behavioural change associated with prevention, improvements in quality of life and evidence that the education programme has reduced or prevented the incidences of PI. 12 The objective is also to focus on providing information that encourages active engagement in patients' selfcare and decision-making. 13 Despite these recommendations, a study by Team et al 14 identified deficits in the uniformity and quality of patient education in the prevention of PIs.…”
Section: Introductionmentioning
confidence: 99%
“…Health literacy is an important element of care for older adults living in the community, in particular, in preventing PIs 12 . Improving health literacy in this area can help enhance the quality of life for the older adults in several ways.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations